Effects of low temperatures on nitrogenase activity in sainfoin (Onobrychis viciifolia) nodulated by arctic rhizobia - Prévost, Danielle; Antoun, H.; Bordeleau, L.M. (FEMS Microbiology Letters, 1987)
The temperate forage legume sainfoin ( Onobrychis viciifolia ) is readly nodulated by rhizobia isolated from arctic legumes ( Astragalus and Oxytropis species). We have investigated the effects of low temperatures on nitrogenase activity in sainfoin nodulated by arctic and temperate (homologous) rhizobia. At low temperatures, nitrogenase activity of arctic rhizobia measured either with detached nodules or with whole plants, was higher than that of temperate rhizobia. At 5°C and 10°C, nitrogenase activity values of arctic rhizobia represented 12% and 33% of those measured at 20°C, while lower values of 3.7% and 22.4% were observed with temperate rhizobia. This cold adaptation was also reflected on bacterial growth where, at 5°C and 10°C, arctic rhizobia showed a shorter doubling time and synthesized more protein than temperate rhizobia.